Information, accesses and use of contraceptive methods and gynecological follow-up between university students (Research, Society and Development, 2022)
Objectives: To identify information, access and use of contraceptive methods and gynecological follow-up among undergraduate nursing students. Method: This is an observational, cross-sectional study with a quantitative approach carried out at a public university in the interior of Minas Gerais. The study was conducted with academics over 18 years of age who agreed to participate in the research. Data collection was performed using an instrument for sociodemographic and economic characterization and on contraceptive methods, information, access, assiduity in the use of contraceptive methods and gynecological consultations. Results: Most of the interviewees use, do not have access difficulties and feel safe with information about contraceptive methods. Most used some method in the first sexual intercourse. The academics hold annual consultations with the gynecologist. Conclusion: The present study allowed us to understand the sexual behavior of nursing students and their access to gynecological consultations, contraceptive methods and information about them. The present study signals to educational institutions the importance of student assistance centers and spaces reserved for the debate of these themes for their academics.